Haciendo hablar a Lisias VII sobre la historia agraria ateniense - Paiaro, Diego (2016)
The 7th speech from the Corpus Lysiacum is, despite its short extension, a source valuable to appreciate different historical questions that are relevant to the classical scholar. This paper focuses on the relation between the referred speech and the rural history of the Athenian democracy. Specifically, an effort is made to balance the data given by the source in order to understand its significance for the study of the private agricultural land leases during the democracy. By the end of the work, it is presented a general methodological reflection about the attitude that contemporary historians should have when they deal with documents from the past.